Psychological distress inequality between employed men and women: A gendered exposure model - Bilodeau, Jaunathan (SSM Popul Health, 2020)
This study examines an exposure model in which the work and family stressors and the access to resources are gendered and contribute to explaining the psychological distress inequality between sex categories, both directly and indirectly through work-family conflict. A multilevel path analysis conducted on a random cross-sectional sample of 2026 Canadians workers from 63 establishments was performed. Our exposure model fully explains the higher level of psychological distress among working women compared to working men. Women are more exposed to work-to-family conflict, have less decision authority, are more likely to be a single parent and have less self-esteem, factors that are directly associated with a higher level of psychological distress. On the other hand, women work fewer hours, have less irregular or evening schedules and have more social resources outside of work, which contribute to lower their level of psychological distress through less work-to-family conflict. By identifying which of the differences in exposure to work and family stressors and resources explain the greater psychological distress of working women compared to working men, and by examining the mediating role of work-family conflict in this process, this study identified specific paths to reduce psychological distress inequality between women and men in the workplace.